Grass Roots’ Voices on the CLIL Implementation in Tertiary Education - Fitriani, Ika (Dinamika Ilmu: Jurnal Pendidikan, 2016)
Twenty-first Century era has brought great challenges in Indonesian education system, i.e. the increasing demand for the students to have foreign language skills to succeed in global world competition. Particularly in the higher education, the awareness of learning English leads some lecturers in Accounting Department Faculty of Economics State University of Malang to apply the concept of Content-and-Language Integrated Learning (CLIL) during the classroom instruction (CLIL) – dual-focused education in which the content subject is delivered through foreign language. It is expected that students are benefited from content and language integration so that they can compete in the real global market. This study, then, elaborated the CLIL practice reflections in Accounting Department as seen from the students’ viewpoint. The data were collected by means of questionnaire and interview. The respondents were students of accounting department class QQ 2012. The result of this current study, then, is aimed at examining students’ general attitude toward CLIL and the effect of English instruction on their language competence. Moreover, the findings in this present study are also intended for evaluating CLIL implementation for further betterment.